'The land does not like them': contesting dispossession in cosmological terms in Mela, south-west Ethiopia. Issue 3 (2nd July 2016) - Buffavand, Lucie
ABSTRACT: The inhabitants of the lower Omo Valley, a lowland area of southwestern Ethiopia, are facing rapid and unprecedented changes due to the implementation of a large-scale development project along the Omo River. The Ethiopian government has undertaken the establishment of a sugarcane plantation of massive proportions and plans to make the local agro-pastoralists into out-growers settled in large, government-designed villages. This paper compares the discourses of the government on the value of local livelihoods with the internal discourses of one local group, the Mela, on the changes affecting the land. It demonstrates that the government and Mela discourses draw on radically different cosmologies and engagements with nature. Whereas the state discourses encapsulate a disenchantment of the world, Mela discourses stress the importance of propitiating mythical beings, held as the 'real custodians' of the land. In Mela's views, their successful engagement with these mythical beings means that they belong to the land, in contrast to the government which they see as neglecting these beings and thus to be doomed to fail in its developmental endeavours. The paper points towards the relevance of these discourses for Mela's sense of agency and autochthonous identity. In the context of an authoritarian state which bridles at open contestation, these discourses provide, in Mela minds at least, a means to subvert state power and to contest its legitimacy and efficiency.